Differences In Counting The Number of Leukocytes Using Cermai Fruit (Phyllantus acidus) Juice and Turk Solution Using The Counting Room Method - Akhmad Rizal Effendi; Gilang Nugraha; Andreas Putro Ragil Santoso (Poltekkes Kemenkes Mataram, 2023)
Leukocytes play a role in the body's defense system. Counting the number of leukocytes can be done manually using turk solution. Glacial acetic acid in turk solution functions to lyse erythrocytes but this compound is included in compounds that are carcinogenic. There is a natural ingredient that can lyse blood cells other than leukocytes, namely Cermai fruit. Cermai fruit contains a weak acid, namely citric acid of 39,8% so that it can lyse blood cells other than leukocytes. This study aims to analyze the difference in the number of leukocytes in cermai fruit juice and turk solution. This type of research is experimental with simple random sampling technique. The sample of this research is cermai fruit which will be used to count the number of leukocytes in 10 respondents. The mean number of leukocytes in the control solution was 6.610 cells/mm3, 10% concentration 4.296 cells/mm3, 20% concentration 4.227 cells/mm3, 30% concentration 5.918 cells/mm3 and 100% concentration 5.745 cells/mm3. Data were analyzed using the Kruskal Wallis test and the sig. 0.001 <0,05 so H1 is accepted, which means there is a significant difference, so it is continued with the Post Hoc test. Post hoc test showed that there was no significant difference in the results of leukocyte counts using cermai fruit with concentrations of 30% and 100% compared to the control (p>0,05). Meaning that only the concentrations of 30% and 100% showed the suitability of the number of leukocytes with the control so that these concentrations could be used as an alternative to 3% glacial acetic acid in turksolution.